2018
DOI: 10.31937/manajemen.v9i2.719
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Financial Leverage terhadap Financial Performance pada Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015

Abstract: The manufacturing sector is one of the most dominant economic sectors in in achieving growth and development in Indonesia. It needs adequate fund to develop its business. The sources of fund are from internal and external. The firm usually optimized the usage of internal fund prior to external fund. The internal fund comes from equity while the external funds are from debt and stock. Debt is also known as financial leverage. There is a phenomenon that the usage of debt increased the firm’s financial performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The results of this study are in accordance with the research results of Arif (2015) as well as Barus (2016) which claimed that debt to asset ratio has a positive and significant effect on return on assets. However, the results of this study are different from the research results conducted by Februansyah & Yanuarti (2017) as well as Gunde et al, (2017) which found that debt to asset ratio has a negative and significant effect on return on assets.…”
Section: The Effect Of Debt To Asset Ratio On Return On Assetscontrasting
confidence: 99%
“…The results of this study are in accordance with the research results of Arif (2015) as well as Barus (2016) which claimed that debt to asset ratio has a positive and significant effect on return on assets. However, the results of this study are different from the research results conducted by Februansyah & Yanuarti (2017) as well as Gunde et al, (2017) which found that debt to asset ratio has a negative and significant effect on return on assets.…”
Section: The Effect Of Debt To Asset Ratio On Return On Assetscontrasting
confidence: 99%
“…Meanwhile, study by Zulaecha (2017) shows that leverage have no significant effect to company performance. Contrast from idea that leverage could boost the financial performance, Februansyah & Yanuarti (2017) shows that debt ratio have negative impact on return on assets (ROA).…”
Section: Introductionmentioning
confidence: 93%
“…This phenomenon shows the two side of debt. On one hand debt are generally accepted as a tools to increasing financial performance, since its interest could reduce the tax payment (Februansyah & Yanuarti, 2017). On the other hand too much debt can cause financial distress in the companies.…”
Section: Figure 1 Indonesian Public Companies' Leverage and Performamentioning
confidence: 99%
“…The impact of total debt and different types of debt, such as bank loans and trade credit, on corporate performance is negative and significant. If the company's overall debt ratio is more than its own capital, the higher the risk that the company must face, which can lead the company to go bankrupt or cause the company to go bankrupt because the firm is not disciplined in paying debts (Februansyah & Yanuarti, 2017). Roden and Lewellen (2002) discovered a positive association between profit and overall debt as a percentage of debt payments in their debt research.…”
Section: Introductionmentioning
confidence: 99%